Peran Organisasi Persatuan Islam Tionghoa Indonesia (Piti) dalam Perkembangan Muslim Tionghoa di Kota Medan Tahun 1998-2023 - Anna Maharani Br Lubis; Sori Monang; M. Nasihudin Ali (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
Chinese Islamic Unity Organization (PITI) is a social missionary organization that houses ethnic Chinese Muslims in the city of Medan which was founded in 1961. In its organizational development it experienced obstacles such as during the New Order era when it had to change the name of its organization. And in 1998, PITI Medan could be said to have